The Influence of CR and DER on ROE in The Non-Cyclical Consumer Sector For Ten Years - Apriliani, Nabila (Indonesian Financial Review, 2023)
This research is a quantitative study to determine the effect of the Current Ratio (CR) and Debt to Equity Ratio (DER) on Return On Equity (ROE) in the Consumer Non-Cylclical Sector for the 2012–2021 period. The data used is secondary data obtained from www.idx.co.id. The sample in this study used a purposive sampling method and obtained as many as 4 companies out of 10 population companies in the industrial sector which were used as research objects. The data analysis method used in this research is descriptive statistics, panel data regression analysis, hypothesis testing, and coefficient of determination test. Based on the partial test analysis, CR has no significant effect on ROE in the non-cyclical consumer sector. Then, DER has a significant effect on Return ROE in the non-cyclical consumer. It is concluded that CR and DER together have no effect on ROE, simultaneously.